Optimization of Operating Conditions for Enhanced Efficiency in Green Ammonia Production toward Sustainable Fertilizer Applications - Balqis Azzahra; Cornelley Kadja Pala; Nayla Amira Andaristi; Ruqoya Akmalia; Yuliana Sinta Rizka Hapsari (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
This study investigates the enhancement of reaction efficiency in green ammonia production through the optimization of operating conditions using Aspen HYSYS simulation. Conventional ammonia synthesis is limited by its high energy demand, driven largely by extreme operating pressures and temperatures as well as the substantial load on compressors. To address these constraints, the process was modified by lowering the operating temperature in the main heating unit (Q‑101) and adjusting compressor pressure and recycle streams, thereby shifting the reaction equilibrium toward product formation while reducing overall energy requirements. Simulation results reveal that decreasing the temperature from 482.5 °C to 368.9 °C significantly increased the molar flow rates of nitrogen, hydrogen, and particularly ammonia, which reached 185.5 kmol/h. This outcome confirms that lower temperatures in an exothermic reaction enhance conversion in accordance with Le Chatelier’s principle. Furthermore, reducing the heat generated during compression lessens the demand on intercoolers and cooling units, improving overall thermal efficiency. The integration of multistage compressors and the recovery of waste heat provide additional gains in energy efficiency. Collectively, these findings demonstrate that relatively simple adjustments to operating parameters can substantially increase ammonia yield, lower energy consumption, and contribute meaningfully to process sustainability, reinforcing the potential of green ammonia as a more efficient and environmentally responsible pathway for low‑carbon fertilizer production. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).